Determination of Oil Biodegradation Activity of Pseudomonas aeruginosa Isolated from Soil and Molecular Detection of Responsible Genes - Al-Hamando, Maysoon Munther (Iraqi Journal of Science, 2023)
This study concerns the isolation of oil degraded bacterial samples from oil polluted soil in Al-Dora refinery/ Baghdad – Iraq. Soil samples (15) were on mineral salt agar medium (MSM) used to screen the oil degrading bacteria by forming clear zones around the colonies. To confirm the degradation of oil by these bacteria, the isolates were inoculated in mineral salt broth, 15 isolates of Pseudomonas spp. was detected from which two isolates identified as P. aeruginosa by morphological, physical and biochemical characteristics that confirmed by using Vitick identification system. Growth was estimated in terms of whole cell by measuring optical density at 620 nm and free extract protein was estimated by protein measurement with Folin phenol reagent method. PCR technique was used to detect the alkB genes from the DNA extracted from the two Pseudomonas aeruginosa isolates.